WORKPLACE DEMOCRACY AND SUPPLY CHAIN DYNAMICS IN THAILAND: MEDIATING ROLE OF EMPLOYEE VOICE - Soonthornpipit, Hathaipan; Yama, Arifeen; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2019)
Effectiveness of supply chain in manufacturing organizations can never be completely efficient without contribution and participation of employees. For such a need, workplace democracy seems the only sane solution to ensure better agility and negotiation at supply side of the firm. This study has aimed to analyze the impact of workplace democracy on supply chain negotiation and agility in mediating role of employee voice. Sample was the employees of different colleges and universities of Thailand. The gathered data was then analyzed on SPSS and AMOS for statistical and hypotheses testing. Results have revealed that workplace democracy have significant impact on both supply chain negotiation and agility. At the same time, employee voice was also found as significant mediator in given relationships. Employee voiceâ??s role as mediator was a unique contribution in literature through this study and it also has important implications for manufacturing sector of Thailand and other countries that they have to nourish democracy at their workplaces. Literature has also enriched with empirical evidence of these novel linkages and future research indications have also been given in this study.